RADAR TEAM (REMAJA TANGGAP DARURAT) AS AN EFFORT TO IMPROVE THE FLOOD DISASTER EMERGENCY SKILLS - Purwaningsih, Septia Tri; Pramudani, Grefima; Azizah, Nela Nur; Pratiwi, Hani Wulandari; Nurmadiana, Mutia (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Bumi Village, Surakarta is one of the areas that are often flooded. The causes of flooding in the village are the overflow of the Premulung River and sedimentation of Jenes River. Flood of course can cause physical and non- physical damage. Flood emergency in the Bumi Village needs immediate action. One of the society elements that has potential to be mobilized in flood disaster emergency is teenagers, so RADAR (Remaja Tanggap Darurat) team building is one of the solutions in prevention and handling flood disaster in Bumi Village, Laweyan. Purpose: To determine the influence of the RADAR team on improving emergency flood disaster in Bumi Village, Laweyan, Surakarta. Method: This study is observational by Cross Sectional design. Primary data obtained by observation, and secondary data obtained from related documents. Result: The success of this study is shown by the increase of knowledge that can be seen from the increase of pretest-postest questionnaires average score, from 11,2 to 23,1. Conclusion: The RADAR (Remaja Tanggap Darurat) team was proven to improve flood disaster emergency skills in the Bumi Village, Laweyan, Surakarta.